Faktor Risiko Perilaku dan Lingkungan dalam Penularan Malaria di Pulau Sebatik, Kabupaten Nunukan, Kalimantan Timur - Wiwik Trapsilowati; Aryani Pujiyanti; K. Sekar Negari (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2016)
Malaria transmission is influenced by several factors, including parasites, human, mosquito and environment. In 2009, slide positive rate (SPR) in Puskesmas Aji Kuning, Sungai Nyamuk and Setabu in Sebatik Island were identified as amount 63,61%, 28,04% and 30,12% respectively, while the target malaria pre-elimination SPR < 5%. The aim of this study was to determine the behavioral and environmental risk factors of malaria transmission. This is a cross sectional study and the number of sample were 101 respondents. The results showed that there was significant association between the habit of using mosquito nets, the habit of using mosquito coils, repellent and others, the respondent's house near breeding mosquitoes habitats and the respondent’s house near the cocoa/coffee plantation with the occurrence of malaria cases. Relative risk (RR) value were 2,0, 2,3, 2,9 and 1,7, respectively. Behavioral risk factors of malaria transmission were the habit of using a mosquito nets and habit of using mosquito coils, repellent and others. Environmental risk of malaria transmission were the house near mosquito breeding habitats, and the house near the cocoa and coffee plantation.